Developing Iranian sub-national primary health care measurement framework: a mixed-method study - Ramin Rezapour; Ardeshir Khosravi; Mostafa Farahbakhsh; Elham Ahmadnezhad; Saber Azami-Aghdash; Jafar Sadegh Tabrizi (BMC, 2023)
Abstract Background Desired health outcomes are more achievable through strong Primary Health Care (PHC). Using comprehensive and scientific tools, decision-makers are guided to formulate better PHC reforms and policies. This study introduces a sub-national framework based on the World Health Organization (WHO) proposed frameworks for the PHC performance measurement. Method By a mixed-method and qualitative approach, the Iranian sub-national PHC Measurement Framework (PHCMF) was developed through a review of the WHO's PHC measurement conceptual framework (for selecting Key Performance Indicators (KPIs)), literature review (academic database), PHC-related national documents, consultations with an advisory committee of national experts (6-meetings), and the Delphi technique for finalizing the framework. Results The Iranian sub-national PHCMF was finalized with 100 KPIs in three components including Health systems determinants, Service Delivery, and Health system objectives. Based on the result chain domain, most KPIs were related to the output (24 KPIs) and the least were related to the input and the process (9 KPIs). Conclusion Regarding the comprehensiveness of the developed measurement framework due to its focus on all PHC operational levers and key aspects of PHC systems' performance, it can be used as a practical tool for assessing and improving the Iranian sub-national PHC system.